Evaluation of Modulators of cAMP-Response in Terms of Their Impact on Cell Cycle and Mitochondrial Activity of Leishmania donovani - Saha, Amrita; Bhattacharjee, Anindita; Vij, Amit; Das, Pijush K.; Bhattacharya, Arijit; Biswas, Arunima (Frontiers in Pharmacology, 2020)
With the identification of novel cAMP binding effector molecules in Trypanosoma, role of cAMP in kinetoplastida parasites gained an intriguing break through. Despite earlier demonstrations of role of cAMP in survival of Leishmania during macrophage infection, there is essential need to specifically clarify involvement of cAMP in various cellular processes in the parasite. In this context, we sought to gain a comprehensive understanding of the effect of cAMP analogs and cAMP- cyclic nucleotide phosphodiesterase (PDE) inhibitors on proliferation of log phase parasites. Administration of both hydrolysable (8-pCPT-cAMP) and non-hydrolysable analogs (Sp-8-pCPT-cAMPS)of cAMP resulted in significant decrease of Leishmania proliferation. Amongst the various PDE inhibitors, etazolate was found to be potently anti-proliferative. BrdU cell proliferation and K/N/F-enumeration microscopic study revealed that both cAMP analogues and selective PDE inhibitors resulted in significant cell cycle arrest at G1 phase with reduced S-phase population. Furthermore, careful examination of the ﬂagellar motility patterns revealed significantly reduced coordinated forward flagellar movement of the promastigotes with a concomitant decrease in cellular ATP levels. Alongside, 8-pCPT-cAMP and PDE inhibitors etazolate and trequinsin showed marked reduction in mitochondrial membrane potential. Treatment of etazolate at subcytotoxic concentration to infected macrophages significantly reduced parasite burden and administration of etazolate to Leishmania-infected BALB/c mice showed reduced liver and spleen parasite burden. Collectively, these results imply involvement of cAMP in various crucial processes paving the avenue for developing potent anti-leishmanial agent.